1984
DOI: 10.1017/s0074180900078347
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Broadening of Compact Low Galactic Latitude Radio Sources

Abstract: Scattering of radio waves off inhomogeneities in electron density in the interstellar medium can produce an apparent broadening in the angular diameter of an intrinsically compact background radio source. The magnitude and distribution of this effect at low galactic latitudes (|b|<5°) is not well known, although several cases suggest substantial broadening in certain directions, such as the Cygnus X region (Anderson et al. 1972), and the galactic center (Davies, Walsh, and Booth 1976). Large scattering in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The scattering effects scale roughly as A' and so should be most readily detected in OH masers at 18 cm wavelength. Early V L B I measurements showed that OH maser spot sizes are indeed greater in more distant sources (Burke et al 1968), and more recent V L B I data confirm this (Kent and Mute1 1982, Dennison et al 1984, Kemball et a1 1988a. The sizes of the OH maser spots are consistent with predictions based on measurements of interstellar scattering in pulsars and compact extragalactic radio continuum sources.…”
Section: Interstellar Scatteringmentioning
confidence: 86%
“…The scattering effects scale roughly as A' and so should be most readily detected in OH masers at 18 cm wavelength. Early V L B I measurements showed that OH maser spot sizes are indeed greater in more distant sources (Burke et al 1968), and more recent V L B I data confirm this (Kent and Mute1 1982, Dennison et al 1984, Kemball et a1 1988a. The sizes of the OH maser spots are consistent with predictions based on measurements of interstellar scattering in pulsars and compact extragalactic radio continuum sources.…”
Section: Interstellar Scatteringmentioning
confidence: 86%